Chameleon : a black box thriller - Adeleke, Remi, 1982- (Adeleke, Remi, 1982- Black box thriller., 2023)
"When a mysterious former South African commando, Lucas Van Groot, begins taking wealthy hostages all over the world, it appears at first to be a typical ransom gambit. However, it soon becomes clear that his "Hostage Inc." venture is manipulating worldwide stock markets and threatening global economic collapse. Enter Black Box, the CIA's elite, secret special operations branch--so surreptitious that not even the Director of CIA is fully privy to the unit's activities. Black Box is composed of highly skilled agents who perform with precision: Chameleons who can transform into myriad characters, Ghosts who are specialists in stealth and surveillance, Wind operatives who are transportation experts, and Aberration agents whose specialty is deep cover for years. Kali Kent, a Nigerian born and Bronxite Chameleon in the Black Box program, leads the hunt for Van Groot. Tracking this ringleader and his cadre of international criminals, the team discovers the South African mastermind is after a much larger prize and the race is on to prevent a worldwide tragedy. Along the way, Kali will have to face the demons from his childhood and reflect on his emotional path that made him the Chameleon that he is today."--